Avaliação da qualidade da água e mapeamento por sensoriamento remoto (Landsat-8/Oli) do compartimento ambiental Corpo Central I da Represa Billings (São Paulo, SP) - Milz, Beatriz [UNIFESP] (2018)
Introduction: The Billings reservoir is the largest reservoir of water in the Metropolitan Region of São Paulo, and its used for public supply, but has low water quality resulting mainly from pollution that comes from the Pinheiros and Tietê rivers, and the disordered occupation of its watershed. Objectives: The study aimed to evaluate the quality of the water on the Central Body I of Billings reservoir and relate to the characteristics of land use and cover in its watershed. Methods: Land use and cover mapping was performed using Landsat-8/OLI satellite imagery in the software Quantum GIS and the Semi-Automatic Classification Plugin. A land use and cover classification map were generated for land areas, and four classification maps for reservoir areas. Water was sampled on the surface in four sampling points, at two different periods: dry (Aug/2016, Aug/2017) and rainy (Jan/2017 and Feb/2018). The variables analyzed were temperature, dissolved oxygen, pH, electrical conductivity, chlorophyll-a, nutrients (phosphorus and nitrogen), and the Trophic State Index was calculated. The statistical analysis of the limnological results was performed using a space-time interaction analysis. Results: The mapping of land use and cover in the Central Body I showed that the predominant class is the urban area. High concentrations of nutrients were obtained at the point near the reversal of the Pinheiros River, intensified during the rainy season. The application of the Trophic State Index showed that the waters of the Central Body I were classified as Hypereutrophic, evidencing the degradation of the water quality in this compartment. Conclusions: The reversion of the Pinheiros River is a determining factor in the degradation of the quality of surface waters of the Central Body I. The seasonal variation influenced the physical, chemical and biological variables of the water quality of the Central Body I.